Reforming of ethanol on Co/Al2O3 catalysts reduced at different temperatures - Ferencz Zsuzsa (JOURNAL OF CATALYSIS, 2018)
Abstract The steam reforming of ethanol was studied at 823 K on 10% Co/Al2O3 samples calcined at 973 K and reduced at different temperatures from 773 K to 1173 K. The catalysts were characterized by XPS, XRD, TPR, Raman and DRIFT spectroscopy. XRD results revealed that spinel structures are detectable after the thermal treatment of Co/Al2O3, which could be attributed mainly to Co3O4 formation. TPR and XPS measurements show that even the high temperature (1173 K) reduction is not sufficient to totally reduce Co to metallic state. The ethanol conversion at 823 K was relatively stable and it was higher than 90% in all cases, but the product distribution as a function of time on stream significantly depended on the reduction temperature. The selectivities of H2, CO2, and CH4 formation decreased in time but those of ethylene, acetone and acetaldehyde increased. The changes became less pronounced when the reduction temperature increased, so the H2, CO, and CO2 selectivities increased while that of ethylene decreased significantly as a function of reduction temperature. XPS measurements revealed a new low binding energy state in the Co 2p3/2 region during the reaction when the samples were reduced at or below 973 K. This feature was assigned to the formation of a very thin Co layer. On the used catalysts reduced at or above 973 K structured carbon was detected. On the XP spectra several carbon species were identified at the beginning of the reaction. A new feature was also found at lower binding energy which became more and more dominant with the exception of Co/Al2O3 reduced at 1173 K. These species could be assigned as CoCx carbide-like structures rather than a structured carbon layer. It was found that the surface carbon formed in the reaction gradually influences the product distribution. The carbon which probably is built in the Co subsurface poisons the reactivity of the metal and the effect of the support comes in the forefront. The structured carbon layer formed on the Co/Al2O3 reduced at high temperature does not influence the hydrogen formation in the ethanol reforming.